Reproduction and population structure of the sea cucumber Holothuria tubulosa in the Dardanelles Strait, Turkey - DERELİ, H. and TÜRK ÇULHA, S. and ÇULHA, M. and ÖZALP, B. H. and TEKİNAY, A. A. (Mediterranean Marine Science, 2015)
In this study, Holothuria tubulosa Gmelin 1791 was investigated from April 2013 to March 2014 in the Dardanelles Strait, to outline the morphological characteristics, reproductive patterns and the relationship between population characteristics and environmental parameters. Between 15 and 30 individuals of this species were sampled monthly from three stations. There was a negative allometry between length and weight, being gutted weight the most reliable measurement for this species. Reproductive patterns of the species were identified the first time for Turkish coasts. By macroscopic examination of the gonads, smallest sizes (gutted length) were measured as 8.4 and 8.1 cm for female and male, respectively. Sex ratio was calculated as 1: 1.1 with differences between seasons. The reproduction of sea cucumbers occurred between August and September after Gonadosomatic Index (GSI) values reached their maximum in July. The species was found down to 10 m depth with a population density of 0.21 / m2, which was rather low compared to previously reported values for Mediterranean populations of this species. There was a high positive correlation between population density and GSI of the species. The highest population density was observed where the largest sea grass meadows are found.